Super man and the poisoned planet - Manning, Matthew K; Vecchio, Luciano (North Mankato, Minn Stone Arch Books, 2012)
In an attempt to force the Daily Planet newspaper to stop wasting paper, Poison Ivy creates a vine of kryptonite that covers the whole building, and a seriously weakened Superman must find a way to stop her before she kills Lois and his other friends
"A Capstone imprint."
English stories
1 2 13
NEW_ZTN_GN
Keywords: Superman -- (Fictitious character) -- Juvenile fiction; Superheroes -- Juvenile fiction; Supervillains -- Juvenile fiction; Superheroes -- Fiction; Supervillains -- Fiction